Electrospun Polydioxanone Loaded With Chloroquine Modulates Template-Induced NET Release and Inflammatory Responses From Human Neutrophils - Fetz, Allison E.; Wallace, Shannon E.; Bowlin, Gary L. (Frontiers in Bioengineering and Biotechnology, 2021)
The implantation of a biomaterial quickly initiates a tissue repair program initially characterized by a neutrophil influx. During the acute inflammatory response, neutrophils release neutrophil extracellular traps (NETs) and secrete soluble signals to modulate the tissue environment. In this work, we evaluated chloroquine diphosphate, an anti-malarial with immunomodulatory and anti-thrombotic effects, as an electrospun biomaterial additive to regulate neutrophil-mediated inflammation. Electrospinning of polydioxanone (PDO) was optimized for rapid chloroquine elution within one hour, and acute neutrophil-biomaterial interactions were evaluated in vitro with fresh human peripheral blood neutrophils at 3 and 6 hours before quantifying the release of NETs and secretion of inflammatory and regenerative factors. Our results indicate that chloroquine suppresses NET release in a biomaterial surface area-dependent manner at the early time point whereas it modulates signal secretion at both early and late time points. More specifically, chloroquine elution down-regulates interleukin 8 (IL-8) and matrix metalloproteinase 9 (MMP-9) secretion while up-regulating hepatocyte growth factor (HGF), vascular endothelial growth factor A (VEGF-A), and interleukin 22 (IL-22) secretion, suggesting a potential shift towards a resolving neutrophil phenotype. Our novel repurposing of chloroquine as a biomaterial additive may therefore have synergistic, immunomodulatory effects that are advantageous for biomaterial-guided in situ tissue regeneration applications.